Predictors of alcohol use disorder in patients with hypertension: a national registry-based cohort study - Jørgen G. Bramness; Torgeir Gilje Lid; Ingeborg Bolstad; Lars Lien; Dawit S. Abebe (BMC Public Health)
Abstract Background Alcohol use disorder (AUD) is often discovered very late or not at all, with a risk of undertreatment. High alcohol consumption may lead to hypertension. and hypertensive patients should be asked about their alcohol use. Our aim was to look at additional risk factors for receiving a diagnosis of AUD in patients with hypertension. Methods Using the Norwegian full coverage patient registry, we investigated all patients who received an ICD-10 diagnosis of hypertension and who were routinely registered in the specialized healthcare services in 2010. These were followed for six years and those who subsequently received an ICD-10 AUD diagnosis were identified. Age, sex and comorbidities found in the patient registry were used as covariates. Results Of the 103 623 patients diagnosed with hypertension in 2010, 1517 (1.46%) were later diagnosed with AUD. Male sex, young age, having several comorbidities, malnutrition and respiratory disease, anxiety, and especially a diagnosis of major depression increased the risk of being diagnosed with AUD in these hypertensive patients. Conclusion Only a small proportion of the hypertensive patients were later diagnosed with AUD, reflecting that patient registries are poor indicators of true AUD prevalence, since AUD is heavily underdiagnosed. However, the current findings suggest that comorbid conditions such as depression, anxiety, malnutrition, and respiratory disease in hypertensive patients should prompt clinicians to assess alcohol use more proactively. This could in turn lead to better care for both those with hypertension and alcohol problems.